2020
DOI: 10.1111/jfpp.14657
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound‐assisted osmotic dehydration of pomegranate seeds ( Punica granatum L.) using response surface methodology

Abstract: The main objective was to investigate the effect of ultrasound‐assisted osmotic dehydration (UOD) pretreatment on the dehydration kinetics and the physicochemical properties of pomegranate seeds using a response surface methodology, in order to optimize the process. Quality attributes of seeds were estimated through the assessment of physical and thermal characteristics. Results showed a good correlation of experimental values with the model. The optimum conditions used for UOD and osmotic dehydration (OD) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Due to sonication, the OD was more intense, hence the loss of turgor pressure and shrinkage of the protoplast along with its separation from the cell wall [113] probably resulted in a decrease in the maximum compression force and an increase of work required to deform the sample. On the contrary, the hardness was not significantly changed in UOD pomegranate arils [24] and pomegranate seeds [100] when compared with OD. The studies carried out on kiwifruits [108] revealed that US pretreatment significantly enhanced the firmness after 120 min of OD, resulting in similar value for samples treated by 20 and 30 min of US+OD than for fresh kiwifruit.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Due to sonication, the OD was more intense, hence the loss of turgor pressure and shrinkage of the protoplast along with its separation from the cell wall [113] probably resulted in a decrease in the maximum compression force and an increase of work required to deform the sample. On the contrary, the hardness was not significantly changed in UOD pomegranate arils [24] and pomegranate seeds [100] when compared with OD. The studies carried out on kiwifruits [108] revealed that US pretreatment significantly enhanced the firmness after 120 min of OD, resulting in similar value for samples treated by 20 and 30 min of US+OD than for fresh kiwifruit.…”
mentioning
confidence: 71%
“…However, for osmotic solution with a concentration of 70% NaCl and US pretreatment in water, diffusivity increased up to 130%. In addition, Bchir et al [100] noticed higher mass transfer rate for UOD of pomegranate seeds in comparison to OD process. On the basis of surface methodology response, the optimum conditions for a higher mass transfer rate were established at 240 min, 60 • Brix and 41 • C for UOD and 240 min, 29 • Brix and 50 • C for OD process.…”
Section: Comparison Of Ultrasound Assisted Osmotic Dehydration To Sonication Treatment-kinetics Aspectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results are close to those observed by Sakooei-Vayghan et al [ 14 ] where OD pretreatment before hot-air drying for 30 and 45 min decreased drying time to 8 and 7 h, respectively for apricot cubes. Moreover, Bchir et al [ 42 ] emphasized that ultrasound-assisted OD reduced the drying time of pomegranate seeds by over 40%. These results showed parallelism with our research.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bchir et al [20] reported the effect of ultrasound assisted osmotic dehydration on the pomegranate seeds. The result showed that the ultrasound pretreatment involves a reduction in the osmotic solution temperature and favoring a reduction in the process cost.…”
Section: Combination Of Ultrasound With Other Technologiesmentioning
confidence: 99%